Growth and Yield of Strawberry (Fragaria ananassa – Sweet Charlie Variety) as Influenced by Gibberellic and Salicylic Acids - Sison, Prolet; Marcelino, Junito (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the effects of Gibberellic acid (GA₃) and Salicylic acid (SA), applied individually and in combination, on the growth and yield performance of the strawberry variety ‘Sweet Charlie.’ A total of nine treatments were tested, including a control (water), two concentrations of GA₃ (75 and 100 ppm), two concentrations of SA (100 and 200 ppm), and their various combinations. The experiment was conducted from September 2024 to March 2025 at Sitio Little Baguio, Chua, Bagumbayan, Sultan Kudarat, using a Randomized Complete Block Design (RCBD) with a single-factor arrangement. Key growth parameters measured included plant height, number of branches and crowns, runner production, and morphological characteristics of runners. Yield-related variables such as number of flowers, days to flowering, fruit number per plant, fruit diameter, and fruit weight were also recorded. Data were analyzed using analysis of variance (ANOVA), and significant differences among treatments were determined through Tukey’s Honestly Significant Difference (HSD) test. Results indicated that treatments combining GA₃ (75 or 100 ppm) with 200 ppm SA significantly enhanced vegetative growth, accelerated flowering, and improved fruit yield compared to the control and other treatments. Specifically, these combinations increased plant height, number of runners, flower count, fruit number, fruit diameter, and total fruit weight per plant. Additionally, the days to flowering were shortened, and the period from flowering to fruit setting was optimized. The findings suggest that the synergistic application of GA₃ and SA at specific concentrations can effectively improve the growth and productivity of ‘Sweet Charlie’ strawberries, offering practical benefits for strawberry cultivation.